2000
DOI: 10.1577/1548-8659(2000)129<0607:eotoro>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thiamine on Reproduction of Atlantic Salmon and a New Hypothesis for Their Extirpation in Lake Ontario

Abstract: Previous researchers demonstrated that a mortality in fry (called Cayuga syndrome) of Atlantic salmon Salmo salar from Cayuga Lake (New York) was associated with low levels of thiamine. They reduced the mortality of fry by bathing or injecting fry with thiamine. We injected four to six gravid female Atlantic salmon with either physiological saline (PS) or PS plus thiamine (7 mg/kg weight) 14-23 d before eggs were stripped, fertilized, and incubated in individual lots. Chemical analyses showed that eggs from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
2
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 14 publications
0
44
2
1
Order By: Relevance
“…However, this value (2.75 nmol/g) was slightly less than the 2.99 nmol/g total thiamine value reported to produce 20% mortality in Lake Ontario Chinook Salmon eggs [31], but the overall high survival of the fry, and the lack of substantial post-hatch mortality, from this spawn appears to indicate that mortality due to thiamine deficiency did not occur. Of the 99 spawns sampled in this study, only three showed survival of less than 90% between hatch and swim-up, which is the most lethal period for thiamine deficiency complex [28]. Of these, the lowest concentration of total egg thiamine was 9.25 nmol/g, much greater than the concentration considered the upper end of the thiamine deficiency complex [28,31], making it unlikely that a lack of thiamine was the cause of fry mortality.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…However, this value (2.75 nmol/g) was slightly less than the 2.99 nmol/g total thiamine value reported to produce 20% mortality in Lake Ontario Chinook Salmon eggs [31], but the overall high survival of the fry, and the lack of substantial post-hatch mortality, from this spawn appears to indicate that mortality due to thiamine deficiency did not occur. Of the 99 spawns sampled in this study, only three showed survival of less than 90% between hatch and swim-up, which is the most lethal period for thiamine deficiency complex [28]. Of these, the lowest concentration of total egg thiamine was 9.25 nmol/g, much greater than the concentration considered the upper end of the thiamine deficiency complex [28,31], making it unlikely that a lack of thiamine was the cause of fry mortality.…”
Section: Discussionmentioning
confidence: 78%
“…Of the 99 spawns sampled in this study, only three showed survival of less than 90% between hatch and swim-up, which is the most lethal period for thiamine deficiency complex [28]. Of these, the lowest concentration of total egg thiamine was 9.25 nmol/g, much greater than the concentration considered the upper end of the thiamine deficiency complex [28,31], making it unlikely that a lack of thiamine was the cause of fry mortality. The adequacy of thiamine levels in Lake Oahe Salmon observed in this study is further supported by the similar hatch to swim-up survival rates of Lake Oahe Salmon eggs to eggs treated with supplemental thiamine from populations with a history of thiamine deficiency complex [15,16,20].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Mortality in fish is brought about by depletion of available thiamine resulting in early mortality syndrome (EMS) (Honeyfield et al, , 2005b. Thus, dietary thiaminase from alewife consumption has been suggested as a major cause of fry mortality in salmonid culture, reproductive failure by stocked lake trout, and extirpation of landlocked Atlantic salmon in Lake Ontario after alewife invasion (Ketola et al, 2000). Recent work has helped strengthen the connection between the affect of alewife consumption and the incidence of EMS in Great Lakes salmonids (Riley et al, 2007(Riley et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%